Teacher participation in the virtual learning environment in a continuous training course on the Common Curricular National Base (Revista Contexto & Educação, 2022)
This study aimed to analyze the process of continuing education of teachers of basic education in a Municipality, on the Common National Curricular Base held in a virtual learning environment (VLE), analyzing the impact of the use of VLE in the construction of knowledge about the theme . The specific objectives were to describe the stages of the course; describe the participation of teachers in the course and interactions in the virtual learning environment; and, from these analyzes, make reflections about the teachers' learning experiences. The study is characterized as a quantitative and qualitative descriptive research, ex post facto, since the analyzes were performed from the data generated by the system. Our conclusions from the analysis of the metadata suggest that: with regard to the description of the course, there was a prevalence of the use of videos and PDF files; in relation to the interactions of teachers with the tutor, there were few and had no mobilizing or social character and referred to doubts with the tools used in the course; with regard to the participation of teachers in the course, the predominance of views and repetitions of evaluative activities is emphasized. Although several activities had multiple entries, the focus on evaluation predominated.